Characteristics and outcomes of fetuses with laterality defects are the current outcomes better? A single center study. (16th February 2021) - Fesslova, Vlasta; Pluchinotta, Francesca; Brankovic, Jelena; Boschetto, Chiara; Piazza, Luciane; Inversetti, Annalisa; Sigismondi, Cristina; Giorgione, Veronica; Frigiola, Alessandro
Abstract: Objective : To analyze the more recent outcomes of fetuses with different laterality defects. Material and methods: Out of 1508 fetuses with congenital heart disease (CHD) diagnosed by echocardiography between January 1995 and December 2015, 94 (6.3%) presented abnormal visceroatrial situs: 42 till December 2002 (group 1, analyzed retrospectively) and 52 since then until December 2015 (group 2, analyzed prospectively). Twenty-one had left isomerism (Lisom), 22 right isomerism (Risom), 16 situs inversus- dextrocardia (SVI-dx), 5 situs inversus- levocardia (SVI-levo), and 30 situs solitus-dextrocardia (SSol-dx). Results: Seventy-six cases (81%) had CHD, more frequently complex atrioventricular defect. Eighteen cases showed normal heart: half of subgroups SVI-dx and SVI-levo, a third of SSol-dx. Postoperative mortality in continuing pregnancy in group 2 was 43.7 versus 40% in group 1, lower in SVs-dx (0 versus 50%) and Lisom (33.3 versus 66.7%), worse in Risom (71.4 versus 25%). Total mortality in group 2 was 48.3 versus 55% in group 1, better in Ssol-dx (37.5 versus 50%) and in Lisom (27.4 versus 71.4%). In isolated forms all but one case are alive. Conclusions: Our fetal cases presented a relevant mortality in both periods. The outcomes were slightly better in a more recent era in SSol and Lisom. What is known about this topic?: Out of laterality defects, the heterotaxies (i.e. left and right isomerism) are known to be associated to a relevant mortality in fetal and neonatal cases. Heterotaxies have a variable position of the heart, but some authors evaluated only those with dextrocardia in their studies on different laterality defects. Controversial data are presented in the literature for the outcomes of fetuses with laterality defects. Many large studies analyzed the data of a very long time period in which it is opinable to compare the results of the treatment, because of a recent improved management and surgical techniques. What does this study add?: Our study presents an experience of a single center with cases of different types of laterality defects observed during a routine fetal echocardiography, not only heterotaxies. The knowledge of different laterality defects and of their characteristics (association with cardiac and extracardiac anomalies or with normal heart) is useful for the prenatal counseling. We compare the postoperative and total mortality in more recent period (since 2003) with respect to the previous era (1995–2002).